Running and osteoarthritis - Willick, S. E.; Hansen, P. A. (Clinics in Sports Medicine, 2010)
The overall health benefits of cardiovascular exercise, such as running, are well established. However, it is also well established that in certain circumstances running can lead to overload injuries of muscle, tendon, and bone. In contrast, it has not been established that running leads to degeneration of articular cartilage, which is the hallmark of osteoarthritis. This article reviews the available literature on the association between running and osteoarthritis, with a focus on clinical epidemiologic studies. The preponderance of clinical reports refutes an association between running and osteoarthritis.